The economic impact of educational training assessed by the Handling Questionnaire with three inhalation devices in asthma and Chronic Obstructive Pulmonary Disease patients - Dal Negro RW; Povero M (Dove Medical Press, 2016)
Roberto W Dal Negro1, Massimiliano Povero2 1National Centre for Respiratory Phamacoeconomics and Pharmacoepidemiology – CESFAR, Verona, 2AdRes Health Economics and Outcome Research, Torino, Italy Background: The usability of inhalation devices depends on several factors, eg, the drug to inhale, device handling, and patients’ training. Usability is then presumed to have economic consequences. Aim: To assess and compare the cost of patients’ training for proper usability of Breezhaler and Genuair (both dry powder inhalers) and Respimat (a soft mist inhaler) in asthma and chronic obstructive pulmonary disease (COPD) outpatients. Methods: The acceptance and handling of the three devices were investigated by means of the Handling Questionnaire. The time spent in specific training for ensuring a proper actuation and the corresponding costs were also calculated. Linear and logistic regressions were used in order to investigate the factors influencing proper handling of the devices. A significance level of P<0.05 was accepted. Results: According to both the patients’ and the nurse’s judgments, Genuair and Respimat were perceived as the easiest devices to use, while Breezhaler required the highest number of attempts for achieving the first proper actuation (2.6 vs 1.6; P<0.0001). The total training cost per patient (including the nurse’s time for demonstration and that for attending the patients’ maneuvers) was €1.38±€1.21. Breezhaler was found to be the most expensive as the cost per patient was €2.35±€1.26, which was three to four times higher than that of Genuair and Respimat (both devices involved a cost of ,€1 per patient, with negligible differences between each other). Asthma and COPD patients showed a similar trend, with better outcomes reported for asthma patients probably due to lower age. Conclusion: Substantial differences were found to exist in patients’ acceptability and handling of the three devices. The economic impact of specific training was also different and strictly related to the comprehension of the procedure for actuation of each device. Respimat as a soft mist inhaler and Genuair as an metered-dose inhaler proved to be the most convenient in economic terms also. Keywords: device usability, patient preference, economic impact of training, Handling Questionnaire, Breezhaler, Genuair, Respimat, bronchial asthma, COPD